Features of building intellectualized economic systems in the paradigm of sustainable development: functional aspect - О. S. Solosich; O. V. Ocheretiana (Економічний вісник Державного вищого навчального закладу Український державний хіміко-технологічний університет)
The growth of sustainable development and intellectualization in business is leading to an increase in conflicts within economic systems that require coordination and integration. This article outlines the crucial steps for implementing intellectualization processes to achieve sustainable development. A system comprising interconnected functional aspects has been established. The principles for integrating the intellectual economy with sustainable development within enterprise activities have been determined by examining their fundamental differences. As the key functional aspects of the analytical study, the technical and technological (covers the technological aspects of building a sustainable production and technical environment of the enterprise), personnel (determines the features of an intellectualized approach to personnel management on the basis of sustainability), financial (characterizes the features of cash management based on an intellectualized approach), informational (determines the key characteristics of the functioning of the intellectual approach and sustainable development in the modern information field), political and legal (covers the issues of the normative and legal dimension of the functioning of enterprises and their respective positioning to the problems of intellectualization and sustainability), marketing (characterizes the conjunctural aspects of sustainable intellectualized development of economic structures) and ecological aspects (explains the place of the ecological component of sustainable development in the system of intellectualized development of the enterprise). This article holds practical significance for enterprises striving to strike a balance between efficaciously executing intellectualization processes and ensuring steadfast sustainable growth, as they seek pertinent actionable insights. The scientific novelty of the article lies in the conceptual integration of the basic provisions of the sustainable development theory and economic security of the enterprise with thorough detailing of the relevant provisions in terms of business entities functional components.